Uncontrolled Movements In A Hemodialysis Patient: A Case Report Of Myoclonic Jerks And Their Clinical Implications - I Gusti Agung Ayu Ary Indah Pertiwi; I Ketut Sumada (Interdisciplinary Social Studies, 2025)
Introduction:Patients undergoing long-term hemodialysis often face not only physiological but also neurological and psychosocial complications. One such neurological manifestation is myoclonic jerks—sudden, involuntary muscle contractions that may reflect underlying biochemical imbalances and are frequently underrecognized. This phenomenon, particularly in patients with comorbid conditions such as hypertension, warrants closer attention due to its potential impact on patient well-being and healthcare outcomes. Methods:This study adopts a qualitative descriptive case study approach with a retrospective review. Clinical data were obtained through medical records, direct observation, and comparative analysis with existing literature. The aim was to explore the interdisciplinary implications of myoclonic movement disorders in the context of chronic kidney disease and long-term hemodialysis. Results:The case involves a 54-year-old male with stage V chronic kidney disease on routine hemodialysis who presented with frequent myoclonic jerks, alongside emergency hypertension, type 2 diabetes mellitus, and pulmonary edema. Symptoms were linked to metabolic disturbances and possible neurotoxicity resulting from uremic toxin accumulation. Symptom control was achieved through combined electrolyte correction and pharmacological management using clonazepam. Discussion:The findings suggest that neurological manifestations in hemodialysis patients must be understood through a multidisciplinary lens integrating medical, neurological, and psychosocial perspectives. Early diagnosis and comprehensive management, including patient education, are essential in improving quality of life. This case also underscores the need for further interdisciplinary research into movement disorders among chronically ill populations, especially within healthcare systems facing increased burden of non-communicable diseases.